Effect of mango seeds as an untraditional source of energy on the productive performance of dairy Damascus goats - El-Sanafawy, Heba A.; Maggiolino, Aristide; El-Esawy, Ghada S.; Riad, Wasef A.; Zeineldin, Mohamed; Abdelmegeid, Mohamed; Seboussi, Rabiha; EL-Nawasany, Lamiaa I.; Elghandour, Mona M. M. Y.; De Palo, Pasquale; Salem, Abdelfattah Z. M. (Frontiers in Veterinary Science, 2023)
Eighteen dairy Damascus goats weighing 38–45 kg live body weight and aged 3–4 years were divided into three groups according to their body weight, with six goats in each group. Yellow corn grain in their concentrate feed mixture was replaced with mango seeds (MS) at levels of 0% MS in group 1 (G1, control), 20% MS in group 2 (G2), and 40% MS in group 3 (G3). The digestibility coefficients of the organic matter, dry matter, crude fiber, crude protein, ether extract, nitrogen-free extract, and total digestible nutrients increased (P < 0.05) upon feeding MS to G2 and G3. The amounts of dry matter, total digestible nutrients, and digestible crude protein required per 1 kg 3.5% fat-corrected milk (FCM) were lower (P < 0.05) in G2 and G3 vs. G1. Actual milk and 3.5% FCM yield increased (P < 0.05) with the increasing MS dietary level. G2 and G3 had the highest significant (P < 0.05) total solids, total protein, non-protein nitrogen, casein, ash, fat, solids not fat, lactose, and calcium contents compared with G1. Replacing yellow corn grain with MS in G2 and G3 significantly (P < 0.05) decreased the cholesterol concentration and AST activity. Feeding MS increased the concentrations of caprioc, caprylic, capric, stearic, oleic, elaidic, and linoleic acids and decreased the concentrations of butyric, laueic, tridecanoic, myristic, myristoleic, pentadecanoic, heptadecanoic, cis-10-Heptadecanoic, cis-11-eicosenoic, linolenic, arachidonic, and lignoseric acids in the milk fat. The results show that the replacement of corn grain with MS improved the digestibility, milk yield, feed conversion, and economic efficiency, with no adverse effects on the performance of Damascus goats.